Modified Cu-ZnO Catalysts Supported on the Mixture of ZnO and Zn-Al Oxide for Methanol Production via Hydrogenation of CO and CO2 Gas Mixture - Song, Hyun-tae; Kim, Hyun Dong; Yang, Yu-jeong; Seo, Jeong Min; Choi, Ye-na; Lee, Kwan-Young; Moon, Dong Ju (한국화학공학회, 2024)
Cu-based catalysts were created using a two-step co-precipitation method, which can produce methanol from synthesis gases (H-2 and CO) that also contain CO2. The catalysts were manufactured by a two-step co-precipitation method and compared with catalysts manufactured by a one-step co-precipitation method. The supports with Zn/Al = 1 (10ZA) and Zn/Al = 2 (20ZA) showed higher ZnAl2O4 ratios than the other catalysts, and the catalysts using these supports showed a similar trend to the ZnAl2O4 ratio. Cu-ZnO/mixture ZnO and ZnAl2O4 catalysts with more ZnAl2O4 (C10Z/20ZA and C20Z/10ZA) showed lower carbon and CO conversion losses and lower sintering of Cu (200) particles at the reaction temperatures (250, 300, and 350 degrees C) than the Cu-ZnO-ZnAl2O4 (C30ZA) catalyst. Cu-ZnO/mixture ZnO and ZnAl2O4 using support with Zn/Al = 2 (C10Z/20ZA) achieved dispersion of Cu (44.2%) and a methanol yield (409.0 g(MeOH)/kg(cat.)/h) at a reaction temperature of 250 degrees C, GHSV of 4,444 h(-1), and 40 bar.